Visualization for Information Retrieval in Regional Distributed Environment - Amany Salama (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
Information retrieval (IR) is the task of representing, storing, organizing, and offering access to information items. The problem for search engines is not only to find topic relevant results, but results consistent with the user’s information need. How to retrieve desired information from the Internet with high efficiency and good effectiveness is become the main concern of internet user-based. The interface of the systems does not help them to perceive the precision of these results. Speed, resources consuming, searching and retrieving process also aren't optimal. The search engine's aim is developing and improving the performance of information retrieval system and gifting the user whatever his culture' level. The proposed system is using information visualization for interface problems, and for improving other side of web IR system's problems, it uses the regional crawler on distributed search environment with conceptual query processing and enhanced vector space information retrieval model (VSM). It is an effective attempt to match renewal user's needs and get a better performance than ordinary system.